The Lisbon ranking for smart sustainable cities in Europe. (January 2019) - Akande, Adeoluwa; Cabral, Pedro; Gomes, Paulo; Casteleyn, Sven
Abstract: There has recently been a conscious push for cities in Europe to be smarter and more sustainable, leading to the need to benchmark these cities' efforts using robust assessment frameworks. This paper ranks 28 European capital cities based on how smart and sustainable they are. Using hierarchical clustering and principal component analysis (PCA), we synthesized 32 indicators into 4 components and computed rank scores. The ranking of European capital cities was based on this rank score. Our results show that Berlin and other Nordic capital cities lead the ranking, while Sofia and Bucharest obtained the lowest rank scores, and are thus not yet on the path of being smart and sustainable. While our city rank scores show little correlation with city size and city population, there is a significant positive correlation with the cities' GDP per inhabitant, which is an indicator for wealth. Lastly, we detect a geographical divide: 12 of the top 14 cities are Western European; 11 of the bottom 14 cities are Eastern European. These results will help cities understand where they stand vis-à-vis other cities, giving policy makers an opportunity to identify areas for improvement while leveraging areas of strength.